2011
DOI: 10.2174/092986711798184253
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and its Receptors in the Human CNS with New Findings - A Mini Review

Abstract: Serotonin (5-hydroxytryptamine, 5-HT) is well known to be closely associated with emotional disorders, such as depression and schizophrenia. The seven main members of 5-HT receptor family including the different subtypes are involved in the functional pathways in the brain and their balance in activity helps to maintain the normal mental stability. As any detrimental changes in the 5-HT system is believed to alter emotion in human, different drugs including serotonin reuptake inhibitors (SSRIs) are nowadays co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Interestingly, if we critically analyze those findings, it is evident that negative results were also present since the beginning but were mostly neglected. Moreover, attempts were made to encompass them in the defect hypothesis through rather complicated explanations, sometimes involving the 5-HT transporter (SERT) and one or more of the 5-HT receptor subtypes (of which there are now 14) discovered and characterized throughout the years 12 14 . Similarly, the function of the genes or genetic polymorphisms that have been continually proposed in depression in the last two decades was not always confirmed subsequently and led to less conclusive or inconclusive hypotheses 15 , 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, if we critically analyze those findings, it is evident that negative results were also present since the beginning but were mostly neglected. Moreover, attempts were made to encompass them in the defect hypothesis through rather complicated explanations, sometimes involving the 5-HT transporter (SERT) and one or more of the 5-HT receptor subtypes (of which there are now 14) discovered and characterized throughout the years 12 14 . Similarly, the function of the genes or genetic polymorphisms that have been continually proposed in depression in the last two decades was not always confirmed subsequently and led to less conclusive or inconclusive hypotheses 15 , 16 .…”
Section: Discussionmentioning
confidence: 99%
“…This clinical reality presents a major challenge to the serotonin theory of depression, and as a result, researchers have begun to focus on delineating the non-mutually exclusive actions of monoamines, neurotrophic factors and neurogenesis; empirical observations suggest these factors can modulate severity and remission in depressive disorders [ 10 , 20 ]. Thus, a modern view of MDD pathogenesis is that it probably involves not only a wide spectrum of central serotonergic deficits, ranging from synthesis, catabolism and reuptake to receptor malfunction [ 21 , 22 ], but it also results from complicated interactions between serotonin and other neurotransmitters, neuropeptides and neurotrophins [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning rare studies on humans, the early expression of various transmitters and peptides has been documented in the human CNS during embryonic and fetal developmental stages, and those also included serotonin and its receptors. Many of these transmitters and peptides, including serotonin, declined during normal and abnormal aging as a consequence of cell death or otherwise [ 12 ]. In accordance with our study, it was shown that the serotonergic medullary neurons sent bulbospinal axons to all laminae of the spinal cord and innervated medullary sensory, motor, autonomic and respiratory nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…The morphogenesis of the human neural tube seems to be influenced by interactions between the neurotransmitters and peptides and neurons already during the early stages of development [ 11 ], including serotonin and its receptors [ 12 ]. The cell bodies of serotonin-expressing cells appear first in the brainstem and mostly project into the spinal cord.…”
Section: Introductionmentioning
confidence: 99%